ANALISIS DAMPAK KOMERSIALISASI PENDIDIKAN & STRATEGI INKLUSIVITAS PADA SEKOLAH DASAR DI WILAYAH URBAN - Fiqra Amaliah ZR; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the impact of educational commercialization and inclusivity strategies in the implementation of elementary education in urban areas. The issue examined arises from the increasing tendency to position education as a commodity, which potentially limits access to and equity in education for students from diverse socio-economic backgrounds. This research employed a qualitative descriptive approach conducted at SD Negeri 18 Kalosi and SD Negeri 103 Kalosi. Data were collected through interviews with school principals, teachers, and parents, observations of student admission processes and learning activities, analysis of school documents, and group discussions with students. The findings indicate that, in general, schools have made efforts to implement principles of equity and inclusivity through student admission policies aligned with government regulations and relatively non-discriminatory learning practices. However, educational commercialization is still evident through differences in school fees, admission selection processes, and limited access to certain activities that require additional financial support, which may hinder the participation of students from underprivileged families. Teachers play a crucial role in reducing these disparities through differentiated instruction, group work, and additional learning support. This study concludes that although inclusivity efforts have been implemented, educational commercialization remains a challenge in achieving equitable and dignified elementary education, thus requiring stronger policy reinforcement and more systematic structural support. Keywords: Educational Commercialization, Educational Inclusivity, Social Justice.